Realność problemu zmiany. Polemika z Adamem Andrzejewskim - Luc, Joanna (Filozofia Nauki, 2017)
The problem of change concerns its inconsistency: according to the principle of indiscernibility of identicals, if two objects are numerically identical, they have the same qualities, so an object cannot change without losing its numerical identity. Andrzejewski (2011) claims that the problem does not even arise, because the principle is false: it links two kinds of identity that are in fact independent. I argue that, despite the apparent independency, numerical identity — in the framework of classical logic — implies qualitative identity, so the principle holds, and thus the problem of change cannot be blocked in this way within this framework.